Effects of Retrofit Strategies on Thermal Comfort and Energy Performance in Social Housing for Current and Future Weather Scenarios - Lucienne G. Basaly; Arman Hashemi; Heba Elsharkawy; Darryl Newport; Nancy Mahmoud Badawy (Buildings)
With growing concerns over energy and heat-related mortality/morbidity rates, enhancing building performances is key to improving the health and well-being of building occupants while reducing CO2 emissions, in line with the UK Government’s Net-Zero targets. This study investigates the impacts of different retrofitting scenarios on overheating risk and energy performance in social housing for current and future climate conditions. Dynamic thermal simulations were carried out using Design Summer Year (DSY) weather files in DesignBuilder software for selected case study buildings. Winter performance was analysed using the Predicted Mean Vote (PMV) index, while summer results were assessed according to the Chartered Institution of Building Services Engineers Technical Memorandum 59 (CIBSE TM59) guidelines. The findings revealed that bedrooms, especially those facing south, were at high risk of overheating. Factors such as building construction, the number of exposed surfaces, and window area influenced the risks. External wall insulation outperformed internal wall insulation in improving summer comfort. In the winter, Passivhaus standards with natural ventilation ensured thermal comfort across all zones, with a 41–53% reduction in heating energy consumption under current weather conditions. The risk of overheating and associated health issues significantly increased for the future weather scenarios. Further investigation into ventilation strategies, occupant behaviour, and passive design is required to mitigate overheating risks while reducing energy consumption in buildings.